Tinjauan Keterlambatan Klaim Berkas BPJS Rawat Inap di RSUP dr. Hasan Sadikin - Lutfiatun Nadibah Herman; Sustin Farlinda; Efri Tri Ardianto; Agus Setiawan Abdurachman (Politeknik Negeri Jember, 2020)
The implementation of the National Health Insurance program in hospitals as referral Health Service Provider in collaborate with the Indonesia Health Insurance Implementing Agency to provided public health services by using a prospective payment system. Based on preliminary study, it known the inpatient claim file had delayed as much 11.38%. Itâ€™s not according to hospital standards that claimed should be 100%. This research aimed to provided a preview the causing factors of delayed inpatient claims at RSUP Dr. Hasan Sadikin Bandung based on 5M management elements. This research was descriptive qualitative with expose the results of interviews and observations that had been done in comparison of the theories available. The results showed that the officers still found difficulties to read the diagnosis and the patient's actions due to doctorâ€™s handwrinting difficult to read, incorrect diagnosis codes and actions due to differences in perception between the coder and the doctor, incomplete claimed files such as the result of the patient's supporting examination. There was no standard operational procedure as regulation of inpatient BPJS claimed requirements, computers that been used in the process of filing claims often experiencing long loading and often experiencing network disruptions so it could reduce the performance of officers. In response to those factors, it needs to make a standar operational procedure for completing claim files, to conduct training specifically about National Health Insurance coding at least once a year and doing maintenance on the computer at least once a month.Â